The Phenomenon of Interpersonal Communication of Unikom Students on the Bumble Application in Searching for Partners - Firdaus, Moch Raihan; Oxcygentry, Oky; Muslimah, Tikka (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study analyzes the interpersonal communication patterns of Bumble app users in finding a partner and identifies the inhibiting factors, based on the Social Penetration Theory by Altman and Taylor. Using a descriptive qualitative method and in-depth interviews with five Unikom Bandung students who use Bumble, this study examines how gradual self-disclosure forms online intimacy. The results show that communication patterns are in line with the stages of Social Penetration Theory: starting from Orientation (formal communication, shallow self-disclosure, influenced by the "first move" feature), continuing to Affective Exploration Exchange (careful self-disclosure increases driven by comfort and reciprocity), then Affective Exchange (casual communication, deep self-disclosure, often changing platforms), until reaching Stable Exchange (peak intimacy, very open communication, potential for real relationships). However, not all interactions reach a stable stage, indicating a process that is not always linear. The inhibiting factors for communication vary: in Orientation due to minimal profile information and difficulty in initiation; in Affective Exploration due to lack of reciprocal self-disclosure and immature trust; in Affective Exchange due to limitations of online media and differences in expectations. Overall, authenticity issues and the lack of face-to-face interactions rich in non-verbal cues are fundamental barriers. The study concludes that Bumble facilitates initial self-disclosure, but optimal validation and relationship depth require a transition to real-world interactions. Suggestions are provided for users, app developers, and future research to improve the effectiveness of online communication in dating.